2019
DOI: 10.1021/acsnano.9b01979
|View full text |Cite
|
Sign up to set email alerts
|

Ferrimagnetic Vortex Nanoring-Mediated Mild Magnetic Hyperthermia Imparts Potent Immunological Effect for Treating Cancer Metastasis

Abstract: Cancer metastasis is a serious concern and a major reason for treatment failure. Herein, we have reported the development of an effective and safe nanotherapeutic strategy that can eradicate primary tumors, inhibit metastasizing to lung, and control the metastasis and growth of distant tumors. Briefly, ferrimagnetic vortex-domain iron oxide nanoring (FVIO)-mediated mild magnetic hyperthermia caused calreticulin (CRT) expression on the 4T1 breast cancer cells. The CRT expression transmitted an "eat-me" signal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
161
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(163 citation statements)
references
References 62 publications
2
161
0
Order By: Relevance
“…Nanoparticle-mediated hyperthermia includes photothermal therapy and magnetic hyperthermia. Studies have found that the combination of ICIs (CTLA-4, PD-L1, IDO) and nanoparticle-mediated hyperthermia can promote antigen capture, enhance ICD effect, inhibit Treg cells' function, promote M1 macrophages' differentiation, recruit several folds of tumor-infiltrating lymphocytes, and achieve lasting memory for the inhibition of tumor growth in primary and distant sites (106)(107)(108)(109)(110)(111)(112)(113)(114). The synergetic role of heat and ICIs is further confirmed by results that enhanced tumor antigen-specific T cell responses and an increased Teff to Treg ratio in distant tumors with a combination of RFA and anti-PD-1 mAb administration (105).…”
Section: Preclinical Data Combining Hyperthermia and Icismentioning
confidence: 99%
“…Nanoparticle-mediated hyperthermia includes photothermal therapy and magnetic hyperthermia. Studies have found that the combination of ICIs (CTLA-4, PD-L1, IDO) and nanoparticle-mediated hyperthermia can promote antigen capture, enhance ICD effect, inhibit Treg cells' function, promote M1 macrophages' differentiation, recruit several folds of tumor-infiltrating lymphocytes, and achieve lasting memory for the inhibition of tumor growth in primary and distant sites (106)(107)(108)(109)(110)(111)(112)(113)(114). The synergetic role of heat and ICIs is further confirmed by results that enhanced tumor antigen-specific T cell responses and an increased Teff to Treg ratio in distant tumors with a combination of RFA and anti-PD-1 mAb administration (105).…”
Section: Preclinical Data Combining Hyperthermia and Icismentioning
confidence: 99%
“…Moreover, the therapeutic effect could be further improved by cooperation with programmed death ligand 1 checkpoint blockade (Figure 2F). In vivo experiments on 4T1 xenograft mice demonstrated the superior therapeutic effectiveness of this method, which not only eradicated the primary tumors, but also inhibited the growth of distant tumors and lung metastasis 29 …”
Section: Mions For Cancer Diagnosis and Therapymentioning
confidence: 99%
“…(F) Illustration of the action mechanism of FVIO‐mediated mild magnetic hyperthermia‐sensitized immune checkpoint therapy. Reproduced with permission 29 . Copyright 2019, American Chemical Society…”
Section: Mions For Cancer Diagnosis and Therapymentioning
confidence: 99%
“…A similar study was conducted by Liu et al, where PEGylated ferrimagnetic vortex nanoring (FVIO) with efficient heat induction due to a vortex‐to‐onion magnetization reversal process that was used for inducing local hyperthermia under AMF ( Figure A). [ 87 ] Successful MHT‐induced tumor cell death was confirmed in 4T1, where early apoptosis (38.42%) and late apoptosis (48.96%) were reported after AMF exposure for 5 min. Furthermore, a calreticulin (CRT) signal that promotes phagocytic uptake of cancer cells by the immune system was upregulated in the FVIO plus AMF group, suggesting FVIO‐mediated hyperthermia induces tumor immunogenic properties.…”
Section: Magnetic‐responsive Nanoparticles To Potentiate Immunotherapymentioning
confidence: 99%